1988
DOI: 10.1073/pnas.85.5.1539
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta mRNA increases during liver regeneration: a possible paracrine mechanism of growth regulation.

Abstract: Transforming growth factor a (TGF-,) is a growth factor with multiple biological properties including stimulation and inhibition of cell proliferation. To determine whether TGF-P is involved in hepatocyte growth responses in vivo, we measured the levels of TGF-8 mRNA in normal liver and during liver regeneration after partial hepatectomy in rats. TGF-8 mRNA increases in the regenerating liver and reaches a peak (about 8 times higher than basal levels) after the major wave of hepatocyte cell division and mitosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
269
1
11

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(293 citation statements)
references
References 24 publications
10
269
1
11
Order By: Relevance
“…This is consistent with the fact that c/ebp α is related with the differentiated state, and in some cells c/ebp α can arrest the proliferative phase [23], [24]. Moreover, the expression of some growth-inhibitory genes, or example, tgf-β and activin a, are also up-regulated and kept high during this period in liver regeneration [25][26][27][28][29]. Here we demonstrated that mfrep-1 maintained at more than 2.5-fold the control level after the wave of DNA synthesis.…”
Section: Discussionsupporting
confidence: 76%
“…This is consistent with the fact that c/ebp α is related with the differentiated state, and in some cells c/ebp α can arrest the proliferative phase [23], [24]. Moreover, the expression of some growth-inhibitory genes, or example, tgf-β and activin a, are also up-regulated and kept high during this period in liver regeneration [25][26][27][28][29]. Here we demonstrated that mfrep-1 maintained at more than 2.5-fold the control level after the wave of DNA synthesis.…”
Section: Discussionsupporting
confidence: 76%
“…Against the background of heightened cell renewal, TGF-~, a powerful inhibitor of hepatocyte proliferation in vitro (51,52), was shown in our current experiments to inhibit ongoing proliferation in addition to reducing further the size of the already atrophic hepatocytes. The other test substances that were without activity in our Eck's fistula experiments but which have been reported to be inhibitory in tissue culture systems were tamoxifen (28), IL-l and IL-2 (53).…”
Section: Discussionsupporting
confidence: 49%
“…were recovered by centrifugation at 13,0001 g for 20 minutes, MATERIALS AND METHODS resuspended in TE buffer (10 mmol/L Tris/HCl [pH 8.0] and 1 mmol/L EDTA) for 1 hour at 65ЊC and then incubated with Culture of Hepatocytes. Six-week-old male Wistar rats (about 170 to 200 g) were used for all the experiments.…”
mentioning
confidence: 99%